A3_10 “Hang on a Minute Lads, I’ve Got a Great Idea…” - Booth, Tim; Ryan, Liam; Karazhov, Dennis (Physics Special Topics, 2011)
<!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This paper analyses one of the stunts completed in the 1969 film The Italian Job and discusses the effect of the mass of the stolen gold on the ability to complete this stunt. It was found that only 2,290,000 (out of 4 million) worth of gold could be stolen in order for an unmodified Mini Cooper to complete the getaway.